Factors Influencing Teaching in International Baccalaureate Middle Years Program in Private and Public Schools in Azerbaijan - Shereni, Tendai Samantha (ADA University, 2022)
International Baccalaureate programs have been on the rise in Azerbaijan over the past decade. Public schools are currently embarking on the implementation of all the programs in the IB program which was once restricted to private schools. I conducted qualitative research to explore the perspectives of teaching on teaching in the Middle Years Program (MYP) and the role of teaching support in their teaching process. For this study, I selected two population groups namely MYP teachers and International Baccalaureate (IB) coordinators from public and private schools in Azerbaijan. This study was conducted with teachers and IB coordinators. The data collection consisted of individual interview protocols and the interview protocols were piloted. The key findings of this study revealed that teaching support and curriculum structure may have affected teachers’ experiences while teaching the MYP in a public school and private school context. Teachers required tremendous support especially when it was their initial experience teaching the MYP curriculum framework which was confirmed by the responses provided by both the teachers and IB coordinator participants. This support is required in the form of IB certification training, curriculum guidance, and collaboration facilitation spearheaded by MYP expert coordinators. According to the teachers, there was a gap in the experience and teaching technique requirements of the MYP and the support needed to meet the standards of teaching, especially in the public schools. Hence, I would recommend that schools initiate training at the onset of the school year especially when the staff consists of inexperienced teachers since the basic pedagogical skills from general teaching qualifications may not meet the requirements of the MYP. Additionally, it is important to acquaint teachers with the basics of the MYP before putting them in the classroom. With the potential absence of training, it may be necessary to allow novice MYP teachers to observe ongoing MYP classes on the subjects that they intend to teach. Comprehensive training may curb problems of lack of teacher collaboration if it exists in the schools and mishandling of the curriculum which in turn may lead to the effective teaching of the MYP.
Keywords: Middle Years Program (MYP).; International Baccalaureate programs.; Education, Higher -- Azerbaijan.; Education, Higher -- Azerbaijan -- Challenges.; Education